KEPATUHAN WAJIB PAJAK MEMEDIASI DETERMINAN PENERIMAAN PAJAK PENGHASILAN - Oktaviani, Rachmawati Meita; Hardiningsih, Pancawati; Srimindari, Ceacilia (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
This study aims to examine and analyze the factors affecting income tax revenues with tax compliance as an intervening variable. The study consists of three independent variables that tax penalties, the service tax authorities, and awareness of the taxpayer. While this research is tied in income tax revenues and intervening variable is tax compliance.This study used purpose sampling technique and survey method with questionnaires in collecting data. Respondent were sampled in this study is an individual taxpayer who performs is 120 respondent in Semarang. Research data analysis using multiple analysis with the path analysis.The results showed that the variable tax penalties and service tax authorities an effect on tax compliance, awareness taxpayer has no effect on tax compliance, tax penalties, awareness of taxpayers and taxpayer compliance effect on income tax revenue, the service tax authorities had no effect on tax revenue income. Tax compliance successfully mediate the relationship between the variables of service tax authorities against income tax revenue. Tax compliance Ã‚Â not successfully mediate the relationship between the tax penalties and awareness taxpayer against income tax revenue.